Role of neostigmine and polyvalent antivenom in Indian common krait (Bungarus caeruleus) bite - A. Anil; Surjit Singh; Ashish Bhalla; Navneet Sharma; Ritesh Agarwal; Ian D. Simpson (Elsevier, 2010)
Summary: Bungarus caeruleus (Indian common krait) bite during monsoons is common in Northwest India. This study was undertaken to find the effectiveness of neostigmine and polyvalent antivenom in improving neuromuscular paralysis following bite. All the consecutive patients admitted between June 2007 and December 2008 with common krait bite, identified either from brought snake or circumstantial evidence were studied. Ten vials of polyvalent antivenom and three doses of 2.5 mg neostigmine at 30 min intervals after administration of 0.6 mg of atropine were administered I.V. and patients were assessed for any improvement in neuroparalysis. Seventy-two patients were admitted during the study period. All the patients except two came from rural areas and were brought between June and September. Sixty-two patients were bitten during the day while clearing bricks, cutting grass or walking. The mean time interval between bite and arrival to hospital was 4.5 h. None of the patients showed any improvement following treatment and all patients developed respiratory paralysis, requiring assisted ventilation. Seventy survived and two died. Neostigmine is ineffective in reversing or improving neuroparalytic features in patients with B. caeruleus bite even at higher dose than normally recommended. Keywords: Snake bites, Antivenoms, Asia, Envenoming, Neostigmine, Neurotoxicity, India